Reflecting on social psychology and global neo-liberal capitalism - Böhmke, Werner (PINS-Psychology in Society, 2024)
BOOK REVIEW McDonald, Matthew & Wearing, Stephen (2013) Social psychology and theories of consumer culture: A political economy perspective. London: Routledge. ISB N 978-0-415-81203-0 pbk. Pages viii + 172.